2018
DOI: 10.1002/mana.201800052
|View full text |Cite
|
Sign up to set email alerts
|

The prescribed Ricci curvature problem on three‐dimensional unimodular Lie groups

Abstract: Let G be a three‐dimensional unimodular Lie group, and let T be a left‐invariant symmetric (0,2)‐tensor field on G. We provide the necessary and sufficient conditions on T for the existence of a pair (g,c) consisting of a left‐invariant Riemannian metric g and a positive constant c such that Ric(g)=cT, where Ric(g) is the Ricci curvature of g. We also discuss the uniqueness of such pairs and show that, in most cases, there exists at most one positive constant c such that Ric(g)=cT is solvable for some left‐inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The first such work, due to Hamilton, appeared in [Ham84], where he showed that for a left-invariant metric T on SU(2) there exists a left-invariant metric g, unique up to scaling, such that (1.2) is satisfied with c > 0. Buttsworth extended this result in [But19] to all signatures of T and all unimodular Lie groups of dimension 3. In this case, the equation may fail to have a solution.…”
Section: Introductionmentioning
confidence: 91%
“…The first such work, due to Hamilton, appeared in [Ham84], where he showed that for a left-invariant metric T on SU(2) there exists a left-invariant metric g, unique up to scaling, such that (1.2) is satisfied with c > 0. Buttsworth extended this result in [But19] to all signatures of T and all unimodular Lie groups of dimension 3. In this case, the equation may fail to have a solution.…”
Section: Introductionmentioning
confidence: 91%
“…The question of solvability of (2.2) was settled by Hamilton and the first-named author in [34,13]. Specifically, the following result holds.…”
Section: Homogeneous Spheresmentioning
confidence: 99%
“…In [13], the first-named author settled the question of the solvability of equation (2.2) for left-invariant Riemannian metrics on unimodular Lie groups in 3 dimensions. We summarise the results in Theorem 4.4 below.…”
Section: Unimodular Lie Groups Of Dimensionmentioning
confidence: 99%
“…The case where M is a homogeneous space G/H has been studied extensively; see the survey [11] and the more recent references [12,25,26,4,3]. In some situations, the equation can be solved explicitly, as shown, e.g., in [31,9]. Assume that T is positive-definite.…”
mentioning
confidence: 99%